2019
DOI: 10.2147/opth.s198846
|View full text |Cite
|
Sign up to set email alerts
|

<p>Self-monitoring of intraocular pressure using Icare HOME tonometry in clinical practice</p>

Abstract: Purpose: To determine the value of self-monitoring of diurnal intraocular pressure (IOP) by Icare Home rebound tonometer in patients with glaucoma and ocular hypertension. Methods: Patients with open-angle glaucoma or ocular hypertension, controlled IOP at office visits, and at least 3 years of follow-up in the glaucoma clinic were included. Progression of glaucoma was based on medical records and defined by documented structural and/or visual field change. Patients were trai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 42 publications
1
14
0
Order By: Relevance
“…Cvenkel et al 36 assessed 117 suspected glaucoma, open-angle glaucoma, or ocular hypertension participants, of which 96 participants (82%) fulfilled requirements for certification. The mean age of participants was 57.4 ± 14.9 years.…”
Section: Icare Home Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…Cvenkel et al 36 assessed 117 suspected glaucoma, open-angle glaucoma, or ocular hypertension participants, of which 96 participants (82%) fulfilled requirements for certification. The mean age of participants was 57.4 ± 14.9 years.…”
Section: Icare Home Characteristicsmentioning
confidence: 99%
“…Cvenkel et al provided the Icare HOME to patients with glaucoma or ocular hypertension and found that eyes with significantly higher average IOP, peak IOP, and higher IOP fluctuation as measured on the Icare HOME were the eyes that showed progression in glaucoma (defined as significant visual field deterioration or optic nerve head/retinal nerve fiber layer changes), despite stable in-office IOP measurements. 36 Additionally, Awadalla et al found that a significant reduction in mean IOP after selective laser trabeculoplasty could be detected when providing Icare HOME devices to patients after their procedure. 37 These studies demonstrate the Icare HOME’s role in obtaining an accurate IOP profile to assist in treatment decision-making, which complement similar findings from our own practice.…”
Section: Clinical Utility Of the Icare Homementioning
confidence: 99%
“…The IOP measurements obtained with RTONE were shown to be strongly correlated with Goldmann applanation tonometer used in clinic visits, and for patients with NTG with a progression that was disproportionate to their office IOP measurements, the use of RTONE can reveal higher IOP spikes which was unidentified during office hours. Therefore, self-tonometry is definitely a valuable adjunct to spot office measurements as it provides a more complete data on the diurnal change of IOP which may assist in glaucoma management [22]. However, it should also be noted that self-tonometry is rather technically challenging for elder glaucoma patients and also could not take sleeping IOP measurements [23].…”
Section: Modalities Of 24-hour Iop Monitoring In Clinical Practicementioning
confidence: 99%
“…Devices which can be used by patients to measure these parameters are still undergoing development and refinement. [ 13 14 ] Hence, “home-tonometry” and “home-perimetry” is still a work in progress. The inability to acquire information regarding IOP, optic disc or visual field changes through a tele-consultation highlights the futility of this interface for the management of chronic glaucoma.…”
Section: Glaucomamentioning
confidence: 99%